In Situ Synthesis and Characterization of 2, 2′‐Methylenebis(6‐tert‐butyl‐4‐ethylphenol)‐Incorporated Polymeric Membranes. Issue 1 (15th October 2013) - Rajesh, Smitha; Murthy, Z. V. P.
ABSTRACT: Synthesis and characterization of asymmetric ultrafiltration membrane made from polysulfone (PS), with an antioxidant 2, 2′‐methylenebis (6‐tert‐butyl‐4‐ethylphenol) (MBEP) as an additive, is reported in this work. The membrane was prepared by phase‐inversion process from casting solution containing PS polymer, dichloromethane solvent, and antioxidant MBEP as an additive. Polyvinylpyrrolidone (2 wt% concentration) was added in the casting solution as pore former. The membrane was characterized in terms of thermogravimetric analysis (TGA), differential scanning calorimetry, oxidative‐induction time test, mechanical measurements and cross‐flow filtration for milk concentration, and scanning electron microscopy (SEM). From TGA, it is noted that volatilization of MBEP started before its boiling point (198°C), indicating that the antioxidant has interacted with the PS, and the results indicate that highest residual weight percentage was obtained for higher weight percent antioxidant filled membrane substantiating its higher thermal stability. From SEM images, it is observed that as MBEP content gets higher dispersion of particles in the membrane, the matrix becomes more homogeneous. The other results revealed that the addition of antioxidant MBEP produced a membrane with higher thermal stability. The presence of additive also affects the surface roughness, membrane morphology, and mechanical strength. © 2013 Wiley Periodicals, Inc. Adv Polym Technol 2014, 33, 21392; View this article online atwileyonlinelibrary.com . DOI 10.1002/adv.21392